Manajemen Pemasaran Berbasis Nilai Persatuan untuk Meningkatkan Loyalitas Konsumen Mahasiswa pada UMKM Seblak Bujangan - Anggi Dwi Cahyani; M. Badru Salam; Unis Fitriani; Nuhiyah Nuhiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to explore the implementation of unity-based marketing management in enhancing consumer loyalty among university students at the Seblak Bujangan culinary microenterprise. As one of the local SMEs located near Sultan Ageng Tirtayasa University, Seblak Bujangan integrates the value of unity—derived from the Third Principle of Pancasila—into its marketing strategy, not only to attract customers but also to create a social space that strengthens community bonds. The research employs a descriptive qualitative method involving interviews, observations, and documentation to gain a deep understanding of marketing practices and their social implications. Findings reveal that Seblak Bujangan has successfully transformed from a simple food stall into a social hub for students by combining friendly service, a comfortable atmosphere, and creative digital marketing such as Instagram and TikTok promotions. The sense of togetherness and inclusivity fosters strong emotional attachment, leading to customer loyalty manifested through repeat visits and positive word-of-mouth. The study concludes that marketing strategies grounded in social and national values can enhance consumer engagement while contributing to social harmony. This approach provides new insights into value-based marketing for SMEs, showing that economic and social functions can coexist to create sustainable consumer relationships.